The distribution of occupational injury in the food industry in Ukraine - Evtushenko, Olga; Volodchenkova, Natalia (My University, 2012)
The aim of this study is to examine and compare all publicly accessible data on occupational injuries in Ukraine in the period from 2003 ... 2011. Despite the decline in Ukraine level, both general and fatal injuries, he remains unacceptably high and exceeds the performance of European countries. In order to establish the most significant and hazards that pose the highest risk of injury, when were analyzed by grouping indicators of injury accidents and fatalities by uniform signs, such as an event, cause, profession of the victim, and defined particle distribution of accidents for each feature . Established traumatic profession in some sectors of the food industry, revealed qualitative and quantitative parameters of reasons and factors that characterize the current state of injury by type of work performed, which makes this topic relevant. Метою цього дослідження є вивчення та порівняння всіх загальнодоступних даних про виробничий травматизм в Україні за період з 2003...2011 років. Незважаючи на зниження в Україні рівня, як загального, так і смертельного травматизму, він залишається неприйнятно високим і перевищує показники європейських країн. З метою встановлення найбільш значущих небезпек та тих, що становлять найбільший ризик травматизму, було проаналізовано показники травматизму, нещасних випадків та смертельних випадків, шляхом групування за єдиними ознаками, такими як подія, причина, професія потерпілого, та визначено розподіл частинок нещасних випадків за кожною ознакою. Встановлено травматичність професій у окремих галузях харчової промисловості, виявлено якісні та кількісні параметри причин та факторів, що характеризують сучасний стан травматизму за видами виконуваної роботи, що робить цю тему актуальною.
Keywords: гігієна праці; безпека праці; occupational hygiene; occupational safety; виробничий травматизм; industrial injuries; кафедра екології та екоменеджменту